2016
DOI: 10.2215/cjn.01050115
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Physical Function in Older Patients on Dialysis

Abstract: Background and objectives In-center hemodialysis (HD) is often the default dialysis modality for older patients. Few centers use assisted peritoneal dialysis (PD), which enables treatment at home. This observational study compared quality of life (QoL) and physical function between older patients on assisted PD and HD.Design, setting, participants, & measurements Patients on assisted PD who were .60 years old and on dialysis for .3 months were recruited and matched to patients on HD (needing hospital transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(177 citation statements)
references
References 42 publications
(46 reference statements)
6
149
1
17
Order By: Relevance
“…This study showed that the frailty score was associated with lower physical function and higher illness intrusiveness and symptom scores; the only difference between the two dialysis modalities was a higher treatment satisfaction score on aPD [12]. Given these findings, we hypothesized that outcomes of QoL and physical function would be similar between older patients on dialysis and suitably matched patients receiving conservative care for ESKD.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study showed that the frailty score was associated with lower physical function and higher illness intrusiveness and symptom scores; the only difference between the two dialysis modalities was a higher treatment satisfaction score on aPD [12]. Given these findings, we hypothesized that outcomes of QoL and physical function would be similar between older patients on dialysis and suitably matched patients receiving conservative care for ESKD.…”
Section: Introductionmentioning
confidence: 94%
“…The FEPOD cohort, which has been previously described [12], consists of older patients on HD and aPD (n ¼ 251). They had been recruited from the same renal centres, between June 2011 and December 2013.…”
Section: Study Design and Recruitmentmentioning
confidence: 99%
“…The morbidity risk is also considerable, with a high prevalence of falls and hospitalization. These issues should be discussed with older patients with advanced kidney disease and their families to allow them choose the most appropriate therapy [28]. Recent reports suggest peritoneal dialysis to be a beneficial treatment strategy for fluid status control in patients with refractory congestive heart failure in terms of hospitalization rates and duration [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…But, cost-effectiveness of assPD compared to in-center (hemo-) dialysis is finally undefined and biased by different mode of calculations and costs included [review by 27]. Nevertheless, in the lack of economical implications level of treatment satisfaction may favour patients´ preferences in assPD modality choice [39].…”
Section: Financial Aspectsmentioning
confidence: 99%
“…Quality of life and physical function in older patients on assPD are equal compared to similar hemodialysis patients, but treatment satisfaction in assPD is higher [39]. This is supported by quality of life assessment in older patients where PD patients experienced less illness and treatment intrusion compared to those on hemodialysis [41].…”
Section: Options Advantages and Future Of Assisted Pdmentioning
confidence: 99%